KORE DİLİ PROGRAMINDA SÖZ VARLIĞININ ÖĞRETİMİ - (:unkn) unknown (My University, 2016)
2000, 2003, 2006 ve 2009 yıllarında yapılan Pisa araştırmalarında okuryazarlık alanında en yüksek başarıya Finlandiya ve Kore (Güney Kore) ulaşmıştır. Bu sonuçlar Fince, Korece gibi eklemeli dillerin; okuma ve zihin becerilerini geliştirme yönüyle diğer dillerden daha etkili olduğunu ortaya koymuştur [1]. Türkçe, Korece gibi Ural-Altay grubunda yer alan eklemeli bir dildir. Bu nedenle Korecenin öğretim sürecini incelemek gerekmektedir. Bir dilin gelişiminin incelenmesinde, üzerinde durulması gereken alanlardan biri de söz varlığı öğretimidir. Söz varlığı, Türkçe program kitabında bir dilde var olan kelime, deyim, atasözü ve diğer sözlerin oluşturduğu bütün olarak tanımlanmıştır (İlköğretim Türkçe öğretim programı, 2008, 158). Bu makalede, Pisa sınavlarında okuma okuryazarlığı alanında en başarılı ülkeler arasında yer alan Kore'nin ana dili öğretim programı incelenmiş, Korece de söz varlığı öğretimi ile ilgili "Başarı Standartları" ve "İçerik Örnekleri" ne yer verilmiştir.

Finland and Korea (South Korea) did manage to reach the highest scores in the years of 2000, 2003, 2006 and 2009 on literacy field of PISA assesments. These results proved that the agglutinative languages such as Finnish and Korean appeared to be more effective than the other languages in terms of developing reading and cognitive skills. Turkish is also an agglutinative language which is listed in the Ural Altaic language group like Korean. Therefore, it is needed to examine teaching processes of Korean. Vocabulary teaching is one of the topics which should be focused on during examining the development of a language. Vocabulary is defined as a whole includes words, idioms, proverbs and other sayings which take place in Turkish language program book. In this article, the language teaching program of Korea which ranks among the most successful countries in reading literacy field in Pisa assesments will be examined and the studies in relation to vocabulary teaching in Korean will be also included.
VOCABULARY TEACHING IN KOREAN LANGUAGE
Keywords: Eğitim, Eğitim Araştırmaları